Genetic diversity and structure of the binturong Arctictis binturong (Carnivora: Viverridae) – status of the elusive Palawan binturong and implications for conservation. Issue 1 (17th October 2019) - Veron, Géraldine; Debruille, Agathe; Kayser, Pauline; Fernandez, Desamarie Antonette P; Bourgeois, Aude
Abstract: The binturong or bearcat is a forest mesocarnivore ranging from Nepal to Indonesia and the Philippines. Several subspecies of binturongs are recognized but a revision is needed. The binturong from Palawan was described as a species and is now considered a subspecies, but its status has never been checked using molecular approaches. Owing to its restricted range and the pressure on its habitat, the Palawan binturong may be endangered. It is, therefore, of crucial importance to clarify its taxonomic status, particularly for the management of captive populations. We sequenced one nuclear and two mitochondrial markers for binturongs from locations across the species range and from zoos. Our results provide an assessment of the genetic polymorphism and structure within the binturong, resulting in two groups, corresponding to the Indochinese and the Sundaic regions. Within the latter were found the Palawan binturongs on one side, and an individual from Sulu archipelago (a locality not reported before) on the other side. The Palawan binturongs form a monophyletic group, genetically close to Bornean binturongs, which suggests that they may have dispersed from Borneo, and represents a lineage worth preserving, but which is not a separate species nor a separate subspecies.